Handmade Guiding Tip Using a Nélaton Tube for Endostapler Application to Pulmonary Vessels - Yang, Shun-Mao; Chen, Jin-Shing; Lee, Jang-Ming (The Thoracic and Cardiovascular Surgeon, 2014)
Pulmonary vessel stapling is the most important but challenging part of thoracoscopic pulmonary lobar and segmental resection. Many thoracoscopy specialists guide the stapler with an introducer to apply staples. Since the introduction of the modified stapler with a curved and angular anvil tip, more surgeons have come to prefer stapling pulmonary vessels without guidance. However, many problems remain with the use of this new product in current clinical practice. Here we propose an easy method with an additional handmade Nélaton tube applied at the anvil tip of the stapler. Through this safe and low-cost modification, pulmonary vessels can be stapled without the aid of an introducer, reducing the possibility of vascular injury during the looping and dividing of the pulmonary vessels by the stapler.
Keywords: lung cancer treatment (surgery medical); pulmonary arteries/veins; surgical equipment (instruments sutures etc.); thoracoscopy/VATS